The Usability, Acceptability, and Functionality of Smart Oral Multidose Dispensing Systems for Medication Adherence: A Scoping Review. (June 2022) - Faisal, Sadaf; Ivo, Jessica; Lee, Catherine; Carter, Caitlin; Patel, Tejal
Background: Medication non-adherence is a leading cause of non-optimal disease management, resulting in poor health outcomes, poor quality of life, and increased healthcare costs. Smart oral multidose dispensing systems (SOMDS) are being developed to address non-adherence; however, little is known about their integration into daily use by patients. Methods: Using Arksey and O'Malley's scoping review framework, relevant literature was searched for in electronic databases (PubMed, EMBASE, International Pharmaceutical Abstracts, and Scopus). Observational and interventional studies reporting the integration and impact on adherence from SOMDS in adults ≥18 years and published after 1960 were included. Results: Thirteen articles including one case study, 8 cohort studies, and 4 randomized trials were eligible. SOMDS included smart blister packaging, automated dispensers, and electronic medication trays. The number of medications dispensed per SOMDS was one (n = 3), >1 (n = 2), placebo (n = 1) and not reported (n = 7). Reported outcomes included impact on medication adherence (n = 3), integration (n = 2) and both parameters (n = 8). Conclusion: Although most studies reported that SOMDS appear usable, there was significant variability in the SOMDS types, patient populations, medication adherence definitions, and measurements; impacting the interpretation of results. Future studies should be designed to address effectiveness of SOMDS on medication adherence in patients with multi-drug therapy and the utilization of real-time adherence data for informing clinical decision making.